Pengaruh Pengetahuan Merek, Asosiasi Merek, Dan Reputasi Merek, Terhadap Keputusan Pembelian (Studi Kasus Pada Sepatu Vans di Kota bogor). - Fauzani M, M Zulfi; Fadillah, Adil (Jurnal Ilmiah Manajemen Kesatuan, 2019)
The number of respondents in this study amounted to 100 respondents taken from consumers who use Vans shoe products and Sneakers Holic in Bogor and the surrounding research data was processed using SPSS version 23. Research methods used is to use quantitative research that places the Product Attributes, Brand Image, And Product Diversification as independent variable and Purchase Intention as a dependent variable. With primary data used is questionnaires distributed to selected respondents and processed the results with statistical calculations. Results Y=16,277 + 0,051 + 0,167 + 0,210 + which in this case means if the Brand Knowledge is 1 (one) then the Buying Decision value will be 0,051. Brand Association is 1 (one) then the Buying Decision will be 0,167. Brand Reputation is 1 (one) then the Buying Decision will be 0,210.